Efficacy and Safety of Oral TDF-Based Pre-exposure Prophylaxis for Men Who Have Sex With Men: A Systematic Review and Meta-Analysis - Huang, Xiaojie; Hou, Jianhua; Song, Aixin; Liu, Xinchao; Yang, Xiaodong; Xu, Junjie; Zhang, Jing; Hu, Qinghai; Chen, Hui; Chen, Yaokai; Meyers, Kathrine; Wu, Hao (Frontiers in Pharmacology, 2018)
Abstract Background: Pre-exposure prophylaxis (PrEP) is used as an HIV prevention method by people at substantial risk of HIV infection. This systematic review and meta-analysis evaluates current clinical evidence for use of oral TDF-based PrEP among men who have sex with men. Methods: A comprehensive literature search in PubMed, web of science, Google Scholar and ClinicalTrials.gov was performed. A random-effects meta-analysis was conducted using the event rate (ER) for estimation of the incidence of HIV and grade 3 or 4 adverse events (AE) among PrEP arm and using risk ratio (RR) for comparison of incidence of HIV and grade 3 or 4 AE between PrEP recipients and PrEP non-users. Blood-based adherence levels were also divided into three categories with reference to previous meta-analysis. Subgroup meta-analysis was also performed to evaluate whether blood-based adherence levels moderated the effect of TDF-based PrEP on HIV incidence. Narrative review was used due to inconsistent measurements of risk behavior and drug resistance. This review is registered on the PROSPERO database (CRD42017077965). Results: Fourteen studies were included in the review. Oral TDF-based PrEP significantly reduced HIV incidence with minimum drug resistance and tolerable safety risks (HIV incidence, ER=1.1%, 95% CI 0.6%-2.0%, p<0.001, RR=0.244, 95% CI 0.111-0.537, p<0.001and grade 3 or 4 AEs, ER=13.0%, 95% CI 9.9%-16.9%, p<0.001, RR=1.059, 95% CI 0.824-1.362, p=0.653). Oral TDF-based PrEP was more effective in reducing HIV incidence with high levels of blood-based PrEP adherence (ER, 0.4%) compared to moderate adherence (2.9%; p<0.001). Most studies found no association between PrEP use and self-reported sexual behavior. Conclusion: Oral TDF-based PrEP is an effective intervention to prevent against HIV infection among MSM. Well-designed implementation science studies that integrate sociobehavioral and biomedical interventions are needed to identify optimal PrEP delivery models in different populations to translate biomedical efficacy into real-world efficacy.